2014
DOI: 10.1074/jbc.m113.520692
|View full text |Cite
|
Sign up to set email alerts
|

Menin Is Required for Optimal Processing of the MicroRNA let-7a

Abstract: Background: Menin represses pancreatic beta cell proliferation. Results: Menin promotes processing of let-7a, whose target IRS2 plays an important role in insulin signaling and beta cell proliferation. Conclusion: Menin represses beta cell proliferation partly via regulation of miRNA biogenesis. Significance: Understanding how menin represses beta cell proliferation will aid toward improving therapies targeting endocrine tumors and metabolic diseases including diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 55 publications
3
24
0
2
Order By: Relevance
“…Remarkably, Vijayaraghavan and colleagues observed that in MIN6 and betalox5 cells, miR‐24 binding to menin mRNA leads to cellular proliferation and improves cell viability . In addition, growing grounds demonstrate that menin plays a decisive role in the processing of certain miRNAs . Taken as a whole, these data point to the existence of a bidirectional crosstalk between miRNA processing and β‐cell development, and further highlight the complexity of the miRNA network involved in pancreas development.…”
Section: Mirnas and The Development Of β‐Cellsmentioning
confidence: 95%
“…Remarkably, Vijayaraghavan and colleagues observed that in MIN6 and betalox5 cells, miR‐24 binding to menin mRNA leads to cellular proliferation and improves cell viability . In addition, growing grounds demonstrate that menin plays a decisive role in the processing of certain miRNAs . Taken as a whole, these data point to the existence of a bidirectional crosstalk between miRNA processing and β‐cell development, and further highlight the complexity of the miRNA network involved in pancreas development.…”
Section: Mirnas and The Development Of β‐Cellsmentioning
confidence: 95%
“…Besides this, genes known to be crucial for parathyroid cell proliferation and hormonal activity regulate miRNA expression in non-parathyroid cells: in the thick ascending limb of Henle, CASR activation by extracellular calcium regulates the expression of miR-9 and miR-374, which in turn inhibit the expression of claudin 14-mediated ultrafiltrated calcium reabsorption [32]; in ectopically expressing menin HEK293 and MEF cells, menin interacts with arsenite-resistant protein 2 (ARS2), a component of the nuclear RNA CAP-binding complex that is crucial for biogenesis of certain miRNAs including let-7a and miR-155 [33]. Therefore, data produced in non-parathyroid cells suggest that the products of the key genes of parathyroid tumours (CASR and menin) modulate the expression of miRNAs that in turn might contribute to the phenotype of parathyroid neoplasia.…”
Section: Micrornas and Potential Gene Targets In Parathyroid Tumoursmentioning
confidence: 99%
“…Menin does not affect levels of primary-let-7a (pri-let-7a), but increases the levels of mature let-7a (Gurung et al 2014). Let-7a targets, including insulin receptor (INSR) and insulin receptor substrate 2 (IRS2), pro-proliferative genes that are crucial for insulin-mediated signaling, are up-regulated in Men1 -excised cells (Gurung et al 2014). Inhibition of let-7a using anti-miRNA in wild type cells is sufficient to enhance the expression of IRS2.…”
Section: Introductionmentioning
confidence: 98%
“…We previously found that menin interacts with arsenite-resistant protein 2 (ARS2), a component of the nuclear RNA CAP-binding complex that is crucial for biogenesis of certain miRNAs including let-7a (Gurung, et al 2014). Menin does not affect levels of primary-let-7a (pri-let-7a), but increases the levels of mature let-7a (Gurung et al 2014).…”
Section: Introductionmentioning
confidence: 99%